Regulation of HPV infection and cervical cancer development following a helminth infection - Butters, Claire (Department of Pathology, 2025)
Soil-transmi,ed helminth (STH) infec7ons elicit systemic immune responses and have the ability to alter suscep7bility to other infec7ons in sites uncolonized by the STH. Recent work published by our group demonstrated that hookworm infec7on increased pathology in the female genital tract (FGT) following infec7on with the commonly sexually transmi,ed herpes simplex virus (HSV)-2. Although epidemiological studies have linked helminth infec7on with an increased prevalence of the most common sexually transmi,ed infec7on, human papillomavirus (HPV), studies in our lab have demonstrated that exposure to helminth products can decrease HPV pseudovirion uptake in vitro. Persistent infec7ons with high-risk types of HPV can result in cervical cancer, the leading cause of cancer related deaths in women in South Africa. Li,le is known about the associa7on between these two diseases. In this thesis, I inves7gated how HPV pseudovirion (PsV) infec7on can be altered by an STH infec7on both in vitro and in vivo. In vitro experiments demonstrated exposure to soma7c helminth an7gens from Nippostrongylus brasiliensis and Heligmosomoides polygyrus bakeri decreased HPV PsV infec7on in two cervical cancer cell lines and one primary kera7nocyte cell line (the target cell of HPV). Similarly, exposure to the excretory-secretory (ES) an7gens from H. polygyrus decreased HPV PsV infec7on in two cell lines, and increased HPV PsV infec7on in the other cervical cancer cell line. When the soma7c an7gens were heat inac7vated, the protec7on against HPV PsV infec7on was abrogated, sugges7ng the molecule involved in this protec7on is a heat unstable protein. In contrast, when H. polygyrus ES an7gen was heat inac7vated, the previously observed increase in infec7on was reversed and instead decreased HPV PsV infec7on. Addi7onally, western blot analysis revealed that exposure to N. brasiliensis soma7c an7gen resulted in increased expression of vimen7n, a molecule known to inhibit HPV infec7on. These results were then validated in vivo, through the development of a physiological murine model for HPV infec7on, u7lising a luminescent HPV PsV and in vivo imaging system (IVIS). Following op7misa7on, I found that HPV PsV infec7on was significantly reduced following intravaginal exposure to N. brasiliensis L3 an7gen and at day 9 post-infec7on with N. brasiliensis. This was associated with a significant increase in eosinophil accumula7on in the female genital tract (FGT) and iliac lymph node (iLN), the draining lymph node of the FGT. Coinfected mice demonstrated a popula7on of eosinophils expressing lower levels of Ly6C and higher levels of CD11b, a recruitment marker. When eosinophil recruitment was blocked, the helminth-dependent reduc7on in HPV infec7on is lost, sugges7ng these immune cells may contribute to this observed protec7on. Addi7onally, western blot analysis revealed that N. brasiliensis infec7on increased the expression of an HPV receptor, glypican. These data suggest that coinfec7on with N. brasiliensis has a protec7ve effect against the ini7al infec7on of HPV. Finally, to inves7gate how STH infec7on may influence the development and growth of HPVrelated cervical cancer, I developed a cervical cancer xenograY model using nude mice. Here, my data suggest that engraYed nude mice infected with N. brasiliensis displayed reduced growth of cervical cancer tumours compared to naïve mice, with no change to tumour immune cell infiltrates but rather an increase in tumour cell p53 expression and altered epithelial to mesenchymal transi7on (EMT) marker expression. Together, these findings show that helminth infec7on can protect against distal viral infec7on and suppress the growth and cancer cell behaviour of HPV associated cervical cancer.